Tindakan Polisi Merazia Warga Masyarakat Yang Tidak Menggunakan Masker Dengan Rotan (Pecut) Saat Covid-19 Di Kota Ambon - Pius Khrisna Eka Putra Naimena; Hendry John Piris; Muhammad Irham (PATTIMURA Law Study Review, 2023)
enforcement so that the actions of these officers violate the police professional code of ethics states that members of the National Police are prohibited from behaving and acting arbitrarily. Formulate the issue of whether the police have the authority to conduct raids and whether the actions of the police using rattan are in accordance with SOPs. The purpose is to review the authority of the police to raid residents who do not use masks during Covid-19 and find out the actions of the Police using rattan in accordance with applicable SOPs in raiding residents during Covid-19. Method of usingnormative juridical law research. By using a statutory approach and a conceptual approach. The legal material is divided into three; Primary legal materials are in the form of other official laws / regulations, secondary legal materials are books and other literature and tertiary legal materials are dictionaries and encyclopedias. Collection of legal materials using literature studies. Management and Analysis of this research is qualitative analysis. The results of the study identified that police law enforcement is regulated in the National Police Law, the police statutory authority is regulated in Law No. 2 of 2002 concerning the National Police, namely maintaining public order, upholding the law, providing protection, protection and community services. Police have procedures including; Appeal to officers so that actions in the field are humanely persuasive, Do not take repressive but humanist actions, Take action against people who do not follow procedures in order to invite and give appeals to the community. Law enforcement raiding residents who do not wear masks with rattan is concluded by the police not in accordance with the rules or sanctions referred to under Perwali Ambon No. 25 of 2020 article 11 in carrying out police actions should not use repressive measures but humanely persuasive in accordance with the direction of the procedure.